PENGARUH BEBAN KERJA TERHADAP NIAT BERPINDAH DIMEDIASI OLEH STRES KERJA PADA PERAWAT - Utami, Sasi; Rahayu, Budi (Universitas Nusantara PGRI Kediri, 2023)
This research examines the effect of workload on desire to change mediated by work stress in nurses at a one of the private hospital in Kediri. The population in this study were all nurses in one of the private hospitals in Kediri. This research is explanatory research with a quantitative approach where data collection was carried out by distributing questionnaires to 126 respondents. Data analysis uses Partial Least Square (SEM-PLS). The research results show that workload and work stress have a significant effect on turnover intention. Likewise, workload has a significant effect on work stress. The results of this study also show that work stress has a significant influence on turnover intention. Furthermore, job stress partially mediates the influence of job insecurity and workload on intention to leave. The results of this research indicate that one of the private hospitals in Kediri can improve its strategy to retain and retain its nurses so they remain in their jobs.